Persistent high incidence of tuberculosis among immigrants in a low-incidence country: Impact of immigrants with early or late latency - Hongbin Guo; Jianhong Wu (Mathematical Biosciences and Engineering)
Spread of tuberculosis (TB) due to the immigration from somedeveloping countries with high TB incidence to developed countriesposes an increasing challenge in the global TB control. Here asimple compartmental TB model with constant immigration, early andlate latency is developed in order to investigate the impact of newimmigrants with latent TB on the overall TB incidence, and tocompare the difference contributed by different proportions oflatently-infected new immigrants with high or low risk to developactive TB shortly after arrival. The global dynamics of the systemis completely classified, numerical simulations are carried out fordifferent scenarios, and potential applications to public healthpolicy are discussed.